#)Giải :
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4,5\right)=3,5\)
\(\Leftrightarrow\left(2x^2-x\right)\left(x+5\right)-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow-5x-4,5=3,5\)
\(\Leftrightarrow-5x=8\)
\(\Leftrightarrow x=-\frac{8}{5}\)
\(x\left(2x-1\right)\left(x+5\right)-\left(2x^2+1\right)\left(x+4,5\right)=3,5\)
\(\Leftrightarrow\left(2x^2-x\right)\left(x+5\right)-\left(2x^3+9x^2+x+4,5\right)=3,5\)
\(\Leftrightarrow2x^3+10x^2-x^2-5x-2x^3-9x^2-x-4,5=3,5\)
\(\Leftrightarrow-6x=8\)
\(\Leftrightarrow x=\frac{-8}{6}=\frac{-4}{3}\)